How do mussel provenance and spat size affect mussel aquaculture performance in the South-Western Mediterranean (Algeria)? - Belgaid Imene; Nacef Lamri; Alioua Zakia; Bachari Nour-El-Islam (Oceanological and Hydrobiological Studies)
The objective of this research was to study the effects of size and spat origin of farmed Mytilus galloprovinciallis in mussel longlines in the east of Bou-Ismail Bay (central coastal Algeria, south-western Mediterranean). The study was conducted from October 2017 to July 2020 in the east of Bou-Ismail Bay. The mussel spat were obtained from four origin sites (Tlemcen, Tenes, Ain Tagourait and the study site) and were seeded on three spat sizes (10–30, 30–60 and >60 mm). The production performance of this species was analysed on 284 random mussel plots using average physical product (APP), gain and loss rates, condition index (CI), percentage of edibility (PE) and shell thickness index (STI). Apart from the CI and loss rate, the performance indicators showed significant differences according to spat size and source (p < 0.05). Overall, the highest APP (4.3) was recorded for the small seeded mussels (10–30) mm and for those originating from Tlemcen, near finfish cages (APP = 4.14). These individuals exhibited more efficient growth and physiology for commercial size and performed better than the spat collected at the study site. The results can be considered a valid contribution to best farming practice for optimising the production of this species in Algeria. It also contributes to the development of integrated multitrophic aquaculture (IMTA) methodology, which is suitable for use in the oligotrophic Western Mediterranean.